Experimental assessment of ladasten and GB-115 effects on the antinociceptive tolerance to morphine - M. A. Konstantinopolsky; I. V. Chernyakova; L. G. Kolik (Фармакокинетика и Фармакодинамика, 2016)
The development of morphine-induced antinociceptive tolerance limits its therapeutic efficacy in pain management. Effects of non-benzodiazepine anxiolytics ladasten and GB-115 on the development of antinociceptive tolerance to morphine were studied in albino male rats. The tolerance was induced by daily sub-chronic administration of morphine (2,0 mg/kg, i.p., twice daily for 5 days) and assessed in immersion tail-flick test on days 1 and 5. Concomitant sub-chronic administration of dipeptide anxiolytic GB-115 (0,1 mg/kg/5 days, i.p.), developed on the base of endogenous tetrapeptide cholecystokinin (CCK), followed by morphine (2,0 mg/kg), reversed the antinociceptive tolerance to morphine on day 5. GB-115 per se at the same anxiolytic dose demonstrated a short-term analgesic activity on days 1 and 5. In contrast, 2-aminoadamantane derivative Ladasten (50,0 mg/kg/5 days, i.p.) with psychostimulant and anxiolytic activity, failed to do so. Ladasten at dose employed in the study, did not exert any effects on pain threshold on days 1 and 5. Our results suggest that in this well-characterized model of acute somatic pain, the development of tolerance to the antinociceptive effect of systemic morphine can be prevented by co-administration with GB-115.